International Students’ Perspectives of Helpful and Hindering Factors in the Initial Stages of a Therapeutic Relationship - Willis-O'Connor, Sariné; Landine, Jeff; Domene, José F. (Canadian Journal of Counselling and Psychotherapy, 2016)
Using interpersonal process recall, 8 international student participants (6 men, 2 women) described what they thought was helpful or hindering to the therapeutic relationship during an analogue initial counselling session. A thematic qualitative analysis revealed that the participants found 5 counsellor qualities and techniques to be helpful to the therapeutic relationship: (a) active listening, (b) casualness, (c) direction, (d) enthusiasm, and (e) connection with client’s culture. Three factors were identified as hindering to the therapeutic relationship: (a) language barriers, (b) fast pace, and (c) counsellor disengagement. Limitations and future directions are discussed.